Collecting qualitative data using digital methods for business and management students - Whiting, Rebecca; Pritchard, Katrina (Mastering business research methods, 2021)
"In Collecting Qualitative Data Using Digital Methods, Rebecca Whiting and Katrina Pritchard provide a concise and accessible guide to a digital data collection method, comprised of tracking and trawling that can be used to collect qualitative data in the fields of business, management and organizational research. With practical guidance and insight into how to use this approach in your own research, this book provides invaluable support to business and management masters students who choose to work with secondary data when completing their dissertations."--Provided by publisher.